Ação cultural na perspectiva freireana: um crivo crítico orientador da relação teatro-escola pública no Sesc São Paulo - Soares, Diego Ferreira Valladares (2024)
This research is part of the research line Public Policies, educational and curricular reforms of the program Education: Curriculum at PUC-SP, within the scope of investigations into Paulo Freire's thought, which deepens the productions of the Paulo Freire Chair at this University. The research analyzed the theatrical actions carried out by Sesc São Paulo in partnership with public schools, with the aim of proposing possible reorientations, in a critical-emancipatory sense, of these cultural actions that represent an important meeting between formal and non[1]formal education. In this analytical path, a bibliography of human and social sciences was reviewed, based on some thematic excerpts. From the field of education and culture, we turn to the works of Paulo Freire and Marilena Chauí. From the field of theater pedagogy, we will draw on the work of Flávio Desgranges, Maria Lucia Pupo and Martha Lemos de Moraes. In this set, the work “Cultural action for freedom and other writings”, by Freire, had centrality and it was from it that connections were made with the others, mainly with regard to the relationships between art, culture and education, as well as, between political culture, cultural policy and democratization of culture. Furthermore, the investigation also focused on a set of data collected through analysis of documents and field evidence, collected in visits and semi-structured interviews. The documents concern Sesc São Paulo and the guidelines of its cultural policy. The field research was carried out in Sesc Units in the city of São Paulo and the interviews were carried out with professionals from this institution involved in carrying out the actions. As analytical resources, prose analysis, a proposal defended by Marli André, and the Freirean conceptual plot, conceived by Ana Maria Saul and Alexandre Saul, were used. It is understood that this research feeds reflections in the field of education and curriculum, as well as contributing to demonstrating, from the angle of the cultural action-education relationship, the relevance of Paulo Freire's thought today. Furthermore, with regard to Sesc and schools, it is believed that the analyzes carried out can contribute to the reorientation of actions carried out in partnership between these institutions, as well as to the construction of the foundations of a path that has, as its horizon, education critical-emancipatory